Aldosterone Blocks Rat Stem Leydig Cell Development In Vitro - Zhang, Jingwei; Huang, Bisheng; Hu, Guanghui; Zhan, Xiangcheng; Xie, Tiancheng; Li, Saiyang; Zhang, Xiaolu; Li, Huitao; Ge, Ren-Shan; Xu, Yunfei (Frontiers in Endocrinology, 2018)
Aldosterone (ALDO) is a primary endogenous mineralocorticoid, appearing as the main hormone controlling sodium and water homeostasis. Its emerging role in the development of many organs has gained interest over the past few years. In the testis, Leydig cells contain mineralocorticoid receptors and ALDO stimulates androgen synthesis via the mineralocorticoid receptors in rat adult Leydig cells. Although ALDO pharmacologically promoted the Leydig cell function, its role in Leydig cell development was unclear. In the present study, we investigated effects of ALDO on rat stem Leydig cell (SLC) proliferation and differentiation. Using an in vitro culture system of the seminiferous tubules from Leydig cell-depleted testis and EdU incorporation into the SLC to judge its DNA synthesis and measurement of medium testosterone production, steroidogenesis-related gene and protein expression, we found that: 1) ALDO suppressed EdU incorporation into SLCs at 100 nM via mineralocorticoid receptor-mediated mechanism; 2) ALDO mainly down-regulated Lhcgr and Scarb1 expression possibly via reducing Leydig cell number. In conclusion, ALDO pharmacologically blocked rat SLC development.